The Impact of Exposure to Violence on Children: A Study of the Psychological Dimensions and Consequences of Experiencing Violence in Childhood” (Al-Academy, 2025)
This study analyzes the psychological, behavioral, and social impact of children’s exposure to violence in media, including television, the internet, and video games. The research adopts a descriptive-analytical method and employs a questionnaire directed at a sample of mothers to assess the correlation between media exposure and child behavior. The results show a strong link between high exposure to violence and increased aggression, anxiety, depression, and learning difficulties. The study highlights the importance of family, school, and community intervention and proposes preventive strategies such as parental monitoring, content regulation, and supportive school programs